Malondialdehyde Acetaldehyde-Adduction Changes Surfactant Protein D Structure and Function - Nissen, Claire G.; Mosley, Deanna D.; Kharbanda, Kusum K.; Katafiasz, Dawn M.; Bailey, Kristina L.; Wyatt, Todd A. (Frontiers in Immunology, 2022)
Alcohol consumption with concurrent cigarette smoking produces malondialdehyde acetaldehyde (MAA)-adducted lung proteins. Lung surfactant protein D (SPD) supports innate immunity via bacterial aggregation and lysis, as well as by enhancing macrophage-binding and phagocytosis. MAA-adducted SPD (SPD-MAA) has negative effects on lung cilia beating, macrophage function, and epithelial cell injury repair. Because changes in SPD multimer structure are known to impact SPD function, we hypothesized that MAA-adduction changes both SPD structure and function. Purified human SPD and SPD-MAA (1 mg/mL) were resolved by gel filtration using Sephadex G-200 and protein concentration of each fraction determined by Bradford assay. Fractions were immobilized onto nitrocellulose by slot blot and assayed by Western blot using antibodies to SPD and to MAA. Binding of SPD and SPD-MAA was determined fluorometrically using GFP-labeled Streptococcus pneumoniae (GFP-SP). Anti-bacterial aggregation of GFP-SP and macrophage bacterial phagocytosis were assayed by microscopy and permeability determined by bacterial phosphatase release. Viral injury was measured as LDH release in RSV-treated airway epithelial cells. Three sizes of SPD were resolved by gel chromatography as monomeric, trimeric, and multimeric forms. SPD multimer was the most prevalent, while the majority of SPD-MAA eluted as trimer and monomer. SPD dose-dependently bound to GFP-SP, but SPD-MAA binding to bacteria was significantly reduced. SPD enhanced, but MAA adduction of SPD prevented, both aggregation and macrophage phagocytosis of GFP-SP. Likewise, SPD increased bacterial permeability while SPD-MAA did not. In the presence of RSV, BEAS-2B cell viability was enhanced by SPD, but not protected by SPD-MAA. Our results demonstrate that MAA adduction changes the quaternary structure of SPD from multimer to trimer and monomer leading to a decrease in the native anti-microbial function of SPD. These findings suggest one mechanism for increased pneumonia observed in alcohol use disorders.